2023
DOI: 10.29303/jppipa.v9i9.3433
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble Technology to Improve Growth of Catfish (Clarias sp.)

Bagus Dwi Hari Setyono,
Lalu Wirahadi Al Baihaqi,
Muhammad Marzuki
et al.

Abstract: Catfish (Clarias sp.) is one of the economically important freshwater fish that has been widely cultivated both traditionally and intensively. Catfish has many advantages such as fast growth, resistance to disease, and can live in water conditions that are low in oxygen content. The use of microbubble technology is expected to support the performance of catfish farming with a biofloc system. With the application of this technology, it is hoped that the oxygen supply from micro-sized air bubbles will increase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Then the final step is observation under a microscope with 100x magnification (Hartika et al, 2014) Survival rate is defined as the comparison between the number of living biota and the total number of biota stocked at the start of the study. The survival rate value can be expressed using the formula according to Setyono et al (2023)…”
Section: Differential Leukocytementioning
confidence: 99%
“…Then the final step is observation under a microscope with 100x magnification (Hartika et al, 2014) Survival rate is defined as the comparison between the number of living biota and the total number of biota stocked at the start of the study. The survival rate value can be expressed using the formula according to Setyono et al (2023)…”
Section: Differential Leukocytementioning
confidence: 99%
“…Poor water conditions can also inhibit fish growth performance. Aquaculture ponds that contain high particles from the left-over feed and fish excretion can increase the NH3, NO2, TDS in water, and decrease the pH and DO, which all these parameters are needed to be in the optimum level to accelerate the fish growth (de Silva et al, 2022;Laza et al, 2021;Setyono et al, 2023). Studies have shown that exposure to suspended sediments can impact the gill structure and microbiome of fish larvae, potentially influencing the distribution patterns of fish assemblages (Hess et al, 2015).…”
Section: Introductionmentioning
confidence: 99%